KADARIYAH AND LAKON SAN PEK ENG TAY IN KETOPRAK - Wiwin, Wiwin Eko Santoso (Satmata: Journal of Historical Education Studies, 2023)
This article is a brief biographical study of one of Yogyakarta's ketoprak artists, Kadariyah. She played the play Sam Pek Eng Tai in the Ketoprak Mataram Mardi Wandowo group (1932-1948). A Chinese play performed in Javanese by the Ketoprak group. This research uses the historical method, which is the search for historical sources including heuristics of both written and oral history sources, source criticism and reconstruction as the historiography stage. Written sources in the form of newspapers or magazines are also used to view historical events. Historical construction or historiography here is based on historical actors as a result of direct interviews with Kadariyah. This research resulted in the finding that stage costumes are not Mesiran, but Chinese costumes. The world of ketoprak is different from the world of opera or toneel drama that presents the play Sam Pek Eng Tai, if the benchmark is the use of language, namely Javanese. Stories are sourced from Chinese chronicles or popular storybooks. Specific studies on Kadariyah with the San Pek Eng Tai play have not been conducted by other researchers.